FROM “EXCUSE ME” TO “HEY”: EVOLUTION OF ATTENTION-GETTING STRATEGIES IN MODERN ENGLISH COMMUNICATION (SCIENCE TIME JOURNAL, 2026)
This article examines the evolution of attention-getting strategies in modern English communication from a pragmatic perspective. It analyzes the shift from traditional politeness-oriented forms such as excuse me to more direct and informal expressions like hey and listen. Using a qualitative corpus-based approach with data from BNC, COCA, and MICASE, the study explores the linguistic forms, pragmatic functions, and contextual use of attention-getting devices. The findings reveal a clear trend toward informalization, highlighting the context-dependent and multifunctional role of attention getting strategies in contemporary English discourse.